Balancing the Psychological Impacts of Career and Parenting among Female Lecturers in Tertiary Institutions in Anambra and Enugu States - Iloakasia, Adaobi Jennifer (Indonesian Journal of Education and Social Humanities, 2024)
This study explores the psychological impacts of balancing career and parenting responsibilities among female lecturers in tertiary institutions in Anambra and Enugu States, Nigeria. The research investigates the stressors that female lecturers face while managing their academic roles and parenting duties, and examines the support provided by tertiary institutions in mitigating these challenges. The study used a descriptive survey approach. The research covered various government-owned institutions, including Nnamdi Azikiwe University, University of Nigeria, Nsukka, and others. Data were collected from 2,297 female lecturers using a validated 4-point Likert scale questionnaire. Analysis involved descriptive statistics and Welch’s ANOVA due to violations of normality and homogeneity of variances. Ethical considerations included obtaining consent from institutional leaders and addressing socio-cultural biases. The findings reveal that female lecturers experience significant psychological distress, including stress, emotional exhaustion, and burnout, due to the dual demands of work and family. Key stressors include long working hours, family responsibilities, childcare challenges, and social expectations of perfect performance. Furthermore, the study identifies the role of tertiary institutions in alleviating these stressors, such as offering flexible work schedules, childcare services, and mentorship programs. Despite these efforts, the study suggests that more comprehensive policies and support systems are needed to improve the work-life balance of female lecturers. The study concludes with recommendations for enhancing institutional support to foster better psychological well-being among female academics.